2010
DOI: 10.3892/or_00000832
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis of tumor suppressor gene PTEN in patients with gastric carcinomas and its impact on PI3K/AKT pathway

Abstract: Abstract. The aim of this study was to clarify the participation of PTEN mutation in gastric carcinogenesis and its impact on PI3K/AKT pathway. All nine exons of PTEN were screened for mutations by direct sequencing in 144 patients with pathologically proven gastric carcinoma and their corresponding normal mucosae, followed by Western blotting to detect the changes in PI3K/AKT pathway. Direct sequencing indicated there were 27 cases with mutations among 144 patients consisting of 15 cases (55.6%) of missense m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Three of the six identified mutations were located in exon 1, two in exon 2, and one in exon 3. The identified mutations were the following: In exon 1: 1, GGAGGAG (54) ATGgGAGGCCGGGC in heterozygous form: this is an insertion of a guanine at position 54; 2, Ser68Term in heterozygous form: this is a nonsense point mutation, where the serine-68 residue changed to stop codon; 3, Asn90Ile heterozygous form: this is a missense mutation with amino acid change (asparagine to isoleucine) at position 90 [ 32 , 33 ]. In exon 2: 4, Gly114Arg in heterozygous form: this is a missense mutation with an amino acid change (glycine to arginine) at position 114 [ 34 ]; 5, Leu153Pro in heterozygous form: this is a missense mutation with an amino acid change (leucine to proline) at position 153 [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three of the six identified mutations were located in exon 1, two in exon 2, and one in exon 3. The identified mutations were the following: In exon 1: 1, GGAGGAG (54) ATGgGAGGCCGGGC in heterozygous form: this is an insertion of a guanine at position 54; 2, Ser68Term in heterozygous form: this is a nonsense point mutation, where the serine-68 residue changed to stop codon; 3, Asn90Ile heterozygous form: this is a missense mutation with amino acid change (asparagine to isoleucine) at position 90 [ 32 , 33 ]. In exon 2: 4, Gly114Arg in heterozygous form: this is a missense mutation with an amino acid change (glycine to arginine) at position 114 [ 34 ]; 5, Leu153Pro in heterozygous form: this is a missense mutation with an amino acid change (leucine to proline) at position 153 [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…PTEN is a negative regulator of the integrin-mediated invasion [ 40 , 46 ]. We also assume that this type of PTEN mutation leads to the inactivation of the PI3K/AKT pathway and may promote tumorigenesis [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One previous study demonstrated that the monoallelic loss of PTEN and PIK3CA amplification is associated with oncogenic activation and may contribute to the malignant progression of gastric cancer [20]. However, there have been several studies estimating the incidence of PI3KCA or PTEN loss in gastric cancer [20,21,22]; none of them reported the predictive value of those markers as clinical markers. In our study, we showed that PTEN loss contributes to an increased risk for progression, even with HER2 inhibitor treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, the receptors of tyrosine kinase (RTKs) (e.g., EGFR and ERBB2) can activate the subunits p110α/β/γ/δ of PI3K, which can subsequently induce the activation by phosphorylation of AKT (p-AKT) through PIP3 or PDK1 [ 24 , 25 , 26 , 27 ]. Conversely, PTEN (a tumor-suppressor phosphatase) can reversely convert PIP3 into PIP2 to avoid AKT activation and maintain a controlled function of this axis in cells [ 18 , 28 , 29 ]. When AKT is phosphorylated, this can inhibit the dimeric protein complex TSC1/TSC2, resulting in the subsequent activation by phosphorylation of mTORC1 (p-mTOR), which induces increased activity of other downstream regulators such as P70S6K1, eIF4E, and 4E-BP1 that have specific cellular roles primordially—but not exclusively—related to cell proliferation, cell growth, and cell cycle progression [ 27 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: The Pi3k/akt/mtor Signaling Pathwaymentioning
confidence: 99%